2020
DOI: 10.1038/s41598-020-72191-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of raffinose metabolism genes uncovers a wild Arachis galactinol synthase conferring tolerance to abiotic stresses

Abstract: Raffinose family oligosaccharides (RFOs) are implicated in plant regulatory mechanisms of abiotic stresses tolerance and, despite their antinutritional proprieties in grain legumes, little information is available about the enzymes involved in RFO metabolism in Fabaceae species. In the present study, the systematic survey of legume proteins belonging to five key enzymes involved in the metabolism of RFOs (galactinol synthase, raffinose synthase, stachyose synthase, alpha-galactosidase, and beta-fructofuranosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 72 publications
(150 reference statements)
2
28
0
Order By: Relevance
“…An interesting outcome was that except for Fru in the pulp, MI in the seeds and peels and Sta in the peels of C. radicans, the levels of almost all NSCs and RFOs analyzed were higher in C. foetidissima. This result suggested speciesspecific differences in carbon partitioning and in the synthesis of RFOs, acting perhaps as abiotic stress-regulating osmolytes and/or seed vigor/seed-desiccation tolerance factors, as reported previously in cucurbits and other plant species [103][104][105][106][107][108][109].…”
Section: Discussionsupporting
confidence: 83%
“…An interesting outcome was that except for Fru in the pulp, MI in the seeds and peels and Sta in the peels of C. radicans, the levels of almost all NSCs and RFOs analyzed were higher in C. foetidissima. This result suggested speciesspecific differences in carbon partitioning and in the synthesis of RFOs, acting perhaps as abiotic stress-regulating osmolytes and/or seed vigor/seed-desiccation tolerance factors, as reported previously in cucurbits and other plant species [103][104][105][106][107][108][109].…”
Section: Discussionsupporting
confidence: 83%
“…Their mode of action involves the protection of membranes from hydroxyl radicals, as they are found between the head groups of lipids. The formation of galactinol from myo-inositol is catalyzed by galactinol synthase, representing the first enzyme that commits carbon toward RFO formation (Vinson et al, 2020). Transcript levels of this gene were only significantly induced in AXSa06-inoculated plants exposed to 200 mM NaCl, indicating an additional role of galactinols as osmoprotectants and stabilizers of cellular membranes, but also as scavengers of ROS under excess salt (Nishizawa et al, 2008).…”
Section: Axsa06 Altered Amino Acid and Sugar Metabolism Imitating Salt Stress Responsesmentioning
confidence: 99%
“…The authors suggested that such behavior is associated with less inhibition of plant growth, restricting excessive ROS accumulation and a consequent lipid peroxidation. Vinson et al (2020), in turn, obtained a transgenic Arabidopsis plant overexpressing AdGolS3 (GOLS candidate gene from A . duranensis ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that such behavior is associated with less inhibition of plant growth, restricting excessive ROS accumulation and a consequent lipid peroxidation. Vinson et al (2020), in turn, obtained a transgenic Arabidopsis plant overexpressing AdGolS3 (GOLS candidate gene from A. duranensis). The genetically modified organism showed increased levels of raffinose and less stress symptoms under drought, osmotic (PEG 6000, 20%), and salt (NaCl, 150 mM) stress.…”
Section: Transcriptionally Constitutive Enzyme Throughout the Assaymentioning
confidence: 99%
See 1 more Smart Citation